Study of a delayed-release system for hard and soft capsules coated with eudragit® s100 acrylic polymers - Luciana Arantes Soares; Eduardo Crema (Acta Scientiarum. Health Sciences, 2020)
The objective of this study was to evaluate a pH-dependent system of ileocolonic release of active ingredients using the polymer Eudragit® S100. A spouted bed was used in the coating process of soft capsules containing palm oil and of hard capsules containing glutamine under standardised experimental conditions. The height and diameter of the palm oil and glutamine capsules were measured using a calliper. The following variables were analysed: Eudragit® S100 dispersion amount used in the capsule coating process, nozzle air pressure, nozzle air flow rate, spray rate and temperature of the spouted bed coating process. The Eudragit® S100 dispersion formulation, trademarked as Quickstart® by Evonik Industries, was used with modifications to prepare the enteric coating. The results showed that the adequate temperature for the spouted bed coating process was 50°C and that 0.2 mL of 6.5% Eudragit® S100 coating per cm2 capsule was resistant for 60 minutes at pH 6.8. The findings demonstrate the pharmaceutical application of Eudragit® S100 in the modification of the coating and the preparation of a delayed-release system of hard and soft capsules, thus enabling ileal release of active ingredients.